Early Childhood Development at TK Aisyiyah Kindergarten: Problems and Solutions - Kiki Zakiah; Susanti; Tini Febriyanti; Herawati Fiqriani (al-Afkar, Journal For Islamic Studies, 2026)
This research intends to examine the problematics and its solutions in early childhood developmental (AUD) at TK Aisyiyah jampang kulon. This study uses a qualitative approach with type of case study. The collecting data uses observation, interview and documentation. While data analysis uses data reduction, data presentation and verification. The results of research that early childhood education is primal period and only comes one time and can’t be repeated. Teachers and parents are obliged to behold physical development of the child, both teachers and parents efforts to stimulate for children. Therefore, as parents must be understand growing and developmental cognitive and psychomotor of their children, and also should understand what children need according to their age, without having forces or violence.